2011
DOI: 10.1590/s1678-77572011000500002
|View full text |Cite
|
Sign up to set email alerts
|

An AMSTAR assessment of the methodological quality of systematic reviews of oral healthcare interventions published in the Journal of Applied Oral Science (JAOS)

Abstract: BackgroundSystematic reviews are not an assembly of anecdotes but a distillation of current best available evidence on a particular topic and as such have an important role to play in evidence-based healthcare. A substantial proportion of these systematic reviews focus on interventions, and are able to provide clinicians with the opportunity to understand and translate the best available evidence on the effects of these healthcare interventions into clinical practice. The importance of systematic reviews in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 20 publications
0
37
0
1
Order By: Relevance
“…Unfortunately, in dentistry 4,5,8 and other biomedical sciences, 6 many published research articles would be considered to have a low LoE. However, LoEs provide an incomplete picture since studies that have the same LoE nominally, may differ in essential methodological aspects (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, in dentistry 4,5,8 and other biomedical sciences, 6 many published research articles would be considered to have a low LoE. However, LoEs provide an incomplete picture since studies that have the same LoE nominally, may differ in essential methodological aspects (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic is an important advantage considering that clinical trials represent a minor portion of research articles in dentistry. 4,5,8 An additional advantage of the MINCIR scale is that it enables one to perform systematic reviews of clinical trials, cohort studies, case-control, and case series studies. 11 The MINCIR scale has been used to assess surgical studies, 6 including studies in the areas of oral and maxillofacial surgery, 8 and has demonstrated psychometric properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three least common topics were restorative dentistry (n=15; 2.3 %), pain (n=11; 1.7 %), and other unclassified studies (n=25; 3.9 %). Although the median number of studies per SR was [15][16][17][18][19][20][21][22][23][24][25][26][27][28], the majority (70.2 %, n=450) included fewer than 24 studies in their review, while 2.0 % (n=13) included more than 100 studies. Most studies failed to describe study characteristics (88.2 %, n = 567), with terms such as Badults^(6.5 %, n = 42) or Bpaediatrics^(5.3 %, n = 34) populations used sparingly among the studies.…”
Section: Description Of Studies Meeting Our Inclusion Criteriamentioning
confidence: 99%
“…For appraising the quality of reviews in this studies, we discussed to give the conditions that the reviews should meet for each question in AMSTAR checklist. To understand the meaning of the AMSTAR question [35] clearly and how to score a review, we consulted correlative reports [35,[41][42][43].…”
Section: Data Assessmentmentioning
confidence: 99%